A Prosopography to Martial’s Epigrams - Moreno Soldevila, Rosario; Fernández Valverde, Juan 19XX-; Marina Castillo, Alberto (De Gruyter, 2019)
A Prosopography to Martial’s Epigrams is the first dictionary of all the characters and personal names found in the work of Marcus Valerius Martialis, containing nearly 1,000 comprehensive entries. Each of them compiles and analyses all the relevant information regarding the characters themselves, as well as the literary implications of their presence in Martial’s poems. Unlike other works of this kind, the book encompasses not only real people, whose positive existence is beyond doubt, but also fictional characters invented by the poet or inherited from the cultural and literary tradition. Its entries provide the passages of the epigrams where the respective characters appear; the general category to which they belong; the full name (in the case of historical characters); onomastic information, especially about frequency, meaning, and etymology; other literary or epigraphical sources; a prosopographical sketch; a discussion of relevant manuscript variants; and a bibliography. Much attention is paid to the literary portrayal of each character and the poetic usages of their names. This reference work is a much needed tool and is intended as a stimulus for further research